Effectiveness of one and two doses of acellular pertussis vaccines against laboratory-confirmed pertussis requiring hospitalisation in infants: Results of the PERTINENT sentinel surveillance system in six EU/EEA countries, December 2015 - December 2019 - Merdrignac, Lore; Aït El Belghiti, Fatima; Pandolfi, Elisabetta; Acosta, Lesly; Fabiánová, Kateřina; Habington, Adele; García Cenoz, Manuel; Bøås, Håkon; Toubiana, Julie; Tozzi, Alberto E; Jordan, Iolanda; Zavadilová, Jana; et al. (Vaccine, 2024)
BACKGROUND: Monitoring effectiveness of pertussis vaccines is necessary to adapt vaccination strategies. PERTINENT, Pertussis in Infants European Network, is an active sentinel surveillance system implemented in 35 hospitals across six EU/EEA countries. We aim to measure pertussis vaccines effectiveness (VE) by dose against hospitalisation in infants aged <1 year. METHODS: From December 2015 to December 2019, participating hospitals recruited all infants with pertussis-like symptoms. Cases were vaccine-eligible infants testing positive for Bordetella pertussis by PCR or culture; controls were those testing negative to all Bordetella spp. For each vaccine dose, we defined an infant as vaccinated if she/he received the corresponding dose >14 days before symptoms. Unvaccinated were those who did not receive any dose. We calculated (one-stage model) pooled VE as 100*(1-odds ratio of vaccination) adjusted for country, onset date (in 3-month categories) and age-group (when sample allowed it). RESULTS: Of 1,393 infants eligible for vaccination, we included 259 cases and 746 controls. Median age was 16 weeks for cases and 19 weeks for controls (p < 0.001). Median birth weight and gestational age were 3,235 g and week 39 for cases, 3,113 g and week 39 for controls. Among cases, 119 (46 %) were vaccinated: 74 with one dose, 37 two doses, 8 three doses. Among controls, 469 (63 %) were vaccinated: 233 with one dose, 206 two doses, 30 three doses. Adjusted VE after at least one dose was 59 % (95 %CI: 36-73). Adjusted VE was 48 % (95 %CI: 5-71) for dose one (416 eligible infants) and 76 % (95 %CI: 43-90) for dose two (258 eligible infants). Only 42 infants were eligible for the third dose. CONCLUSIONS: Our results suggest moderate one-dose and two-dose VE in infants. Larger sample size would allow more precise estimates for dose one, two and three.
Keywords: pertuse; hospitalizace; vakcinace; Sentinel Surveillance; pertusová vakcína; sentinelová surveillance; lidé; Female; Vaccination; Infant; Case-Control Studies; kojenec; Pertussis Vaccine; Whooping Cough; Hospitalization; studie případů a kontrol; ženské pohlaví; Humans